2014
DOI: 10.1371/journal.pone.0107108
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Multidimensional Health Locus of Control Scale Form C in a Non-Western Culture

Abstract: Form C of the Multidimensional Health Locus of Control Scales (MHLC-C) was designed to investigate health-related control beliefs of persons with an existing medical condition. The aim of the present study was to examine the psychometric properties of this instrument in a culture characterized by external control beliefs and learned helplessness—contrary to the societal context of original test development. Altogether, 374 Hungarian patients with cancer, irritable bowel syndrome, diabetes, and cardiovascular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
8
0
2
Order By: Relevance
“…The concepts of "health literacy" and "health-related locus of control" seem to be relevant when attempting to understand the empowerment of human participants in research (27,28). This needs to be explored further in the context of healthrelated decision-making and research participation among the three categories of people that emerged from this study.…”
Section: Moving Forwardmentioning
confidence: 96%
“…The concepts of "health literacy" and "health-related locus of control" seem to be relevant when attempting to understand the empowerment of human participants in research (27,28). This needs to be explored further in the context of healthrelated decision-making and research participation among the three categories of people that emerged from this study.…”
Section: Moving Forwardmentioning
confidence: 96%
“…We used the maximum likelihood (ML) as a factor extraction method and to consider that a model had at least an acceptable fit, we determined that the comparative fit index (CFI) value should be 0.90 or greater, that the root mean square error of approximation (RMSEA) value should be 0.08 or lower, and that the standardized root mean residual (SRMR) should be less than 0.10 (Schweizer, 2010). The models tested were (1) the original four-factor model proposed by Wallston et al (1994), which has been supported by a number of studies (De Las Cuevas et al, 2015; Lundgren et al, 2007; Pereira et al, 2011; Ubbiali et al, 2008), and (2) a three-factor model where items from the Doctors and Other People scales are included in the same scale (Jomeen and Martin, 2005; Konkolÿ Thege et al, 2014).…”
Section: Methodsmentioning
confidence: 93%
“…However, the findings regarding the factor structure of the MHLC-C scales are not consistent. For example, at least two studies with adults have supported a three-factor solution in samples of adult patients with conditions such as cancer, irritable bowel syndrome, or diabetes (Jomeen and Martin, 2005; Konkolÿ Thege et al, 2014). In addition, Ip and Martin (2006) found in a sample of pregnant women that neither the four- or three-factor solution could be supported.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Chance HLC is usually associated with worse indicators of health or disease, while an internal locus of control is associated with positive indicators of health and disease. 3,7,12,13,15,17,18,34,35,36 Thus, dental patients with these profiles are more likely to accept medical or dental approaches and advice, 6 and this correlation may be used strategically by health professionals. Though the results are promising, those involving the "pure internal," "pure powerful others," and "yea-sayer" profiles require a closer scrutiny.…”
Section: Discussionmentioning
confidence: 99%